A retrospective review of great ape cardiovascular disease epidemiology and pathology - Strong, Victoria J.; Martin, M.; Redrobe, S.; White, K.; Baiker, Kerstin (Wiley, 2018)
Cardiovascular disease is associated with significant mortality in zoo-housed great apes and yet little is know about its epidemiology and aetiopathogenesis, and therefore its diagnosis, treatment and prevention. In this retrospective study, the frequency and patterns of cardiovascular disease associated mortality in zoo-housed great apes is explored. Data relating to 71 great apes [Bonobos Pan paniscus (n = 13), Chimpanzees Pan troglodytes (n = 37), Western lowland gorillas Gorilla gorilla gorilla (n = 15), and Bornean orangutans Pongo pygmaeus and Sumatran orangutans Pongo abelii (n = 6)], which died between 2004 and 2014, were studied and key information relating to their signalment (taxa, age, sex), and manner and cause of death analysed. Male sex and increasing age were found to be associated with an increased risk of cardiovascular disease associated death. Relative to the other taxa, orangutans appeared to be less at risk of heart-disease associated mortality. Deaths were often found to be sudden and unexpected. Cardiomyopathies were the most frequently diagnosed cardiovascular disorder. Of these, a group of cardiomyopathies characterized by the presence of myocardial fibrosis were most common, although there were inconsistencies with regards the reporting of other histopathological features. The study identified potential risk factors involved in great ape cardiovascular disease aetiopathogenesis which warrant further exploration. The findings also suggest a need for proactive screening to identify those affected earlier in the disease course. Finally, the study highlights a critical need for improvements to be made to the current approach to post-mortem investigation of great ape heart disease and the subsequent reporting of cardiovascular lesions.